2013
DOI: 10.3892/mmr.2013.1380
|View full text |Cite
|
Sign up to set email alerts
|

Crude extract of Euphorbia formosana inhibits the migration and invasion of DU145 human prostate cancer cells: The role of matrix metalloproteinase-2/9 inhibition via the MAPK signaling pathway

Abstract: Abstract. Prostate cancer is a common worldwide health problem in males with a poor prognosis due in part to tumor invasion and migration. The crude extract of Euphorbia formosana (CEEF) has been used for the treatment of numerous diseases, however, its effects on the migration and invasion of prostate cancer cells have yet to be examined. In the present study, we investigated the effects of CEEF on the migration and invasion of DU145 human prostate cancer cells in vitro. The wound healing assay and the Matrig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…In our study, we found that triticumoside significantly suppressed MMP2/9 mRNA expression in a dose-dependent manner. In line with our results, one study showed that crude extract of Euphorbia formosana inhibits MMP2/9 expression in DU145 human prostate cancer cells to inhibit their migration, suggesting that the extract acts as an antimetastatic agent [20].…”
Section: Discussionsupporting
confidence: 76%
“…In our study, we found that triticumoside significantly suppressed MMP2/9 mRNA expression in a dose-dependent manner. In line with our results, one study showed that crude extract of Euphorbia formosana inhibits MMP2/9 expression in DU145 human prostate cancer cells to inhibit their migration, suggesting that the extract acts as an antimetastatic agent [20].…”
Section: Discussionsupporting
confidence: 76%
“…Recent studies showed that SFN inhibited MMP-2 expression in some tumor cell lines [11], [12]. Moreover, our previous studies and others have confirmed that MMP-2 was the downstream effector of ERK1/2 [27], [28], [33], [34]. Therefore, we proposed that SFN might down-regulate MMP-2 via activating ERK1/2 signaling pathway.…”
Section: Introductionmentioning
confidence: 57%
“…MMPs are crucial factors in the invasion and metastasis of prostate cancer cells (13). This study revealed that the overexpression of DUSP6 inhibited MMP-3 expression in DU-145 cells, whereas DUSP6-knockdown enhanced MMP-3 expression in LNCap cells (Fig.…”
Section: Dusp6 Reduces the Expression Of Mmp-3 And Il-8 In Prostate Cmentioning
confidence: 68%